2013
DOI: 10.1155/2013/142680
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis: From Magnocellular to Cognitive Residual Dysfunction

Abstract: Abstract. Optic Neuritis (ON) has been associated to both parvocellular dysfunction and to an alteration of the magnocellular pathway. After objective visual field and acuity recovery, ON patients may complain about their vision suggesting a residual subclinical deficit. To better characterize visual abnormalities, 8 patients recovering from a first ON episode as well as 16 healthy controls performed a simple detection task and a more complex categorization task of images presented in low spatial frequencies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Such improvement has already been observed in several studies, independently from BCVA changes (Sugiura et al, 2014). While low spatial frequencies are typically impaired by optic neuritis (Viret et al, 2013), high spatial frequencies tend to be altered by intra‐ocular affections, including retinal diseases like age‐related macular degeneration (Peyrin et al, 2017). This might support the hypothesis that ERM surgery was responsible for the contrast sensitivity improvement measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such improvement has already been observed in several studies, independently from BCVA changes (Sugiura et al, 2014). While low spatial frequencies are typically impaired by optic neuritis (Viret et al, 2013), high spatial frequencies tend to be altered by intra‐ocular affections, including retinal diseases like age‐related macular degeneration (Peyrin et al, 2017). This might support the hypothesis that ERM surgery was responsible for the contrast sensitivity improvement measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuritis is associated with alteration of both the parvocellular and magnocellular pathways (194). Viret et al suggested that the more heavily myelinated magnocellular axons are more vulnerable in patients with optic neuritis because low spatial frequencies, which are transmitted by the magnocellular pathway, are affected predominantly 1 month after the acute phase of the optic neuritis episode (195). Despite the recovery of visual acuity, the magnocellular pathway did not fully normalise (196).…”
Section: Acquired Optic Neuropathiesmentioning
confidence: 99%
“…At the lowest level of visual processing, unilateral lesion of the optic nerve is responsible for monocular blindness. Optic neuritis as observed in multiple sclerosis can result in monocular blindness (Viret et al, 2013 ; see Figure 5B1 ). Lesion of optic chiasma, which can be seen in hypophyseal adenoma, results in bitemporal hemianopia: only fibers from nasal retinas decussating in the optic chiasma are injured, resulting in temporal loss of vision bilaterally (Schneider, 1979 ; Foroozan, 2003 ; see Figure 5B2 ).…”
Section: The Blind Brain From Optic Neuritis To Neglectmentioning
confidence: 99%